Application of layout redefinition and computational simulation in a manufacturing environment - Araujo, Andressa Clara Barbosa de; Almeida, Kalil Figueiredo; Santos, André de Mendonça; Santos, Riany Araujo dos; Barreto, Óliver Silva Costa; Damm, Djoille Denner (Brazilian Journal of Production Engineering, 2025)
The physical layout of an industrial plant is a determining factor for the efficiency of production processes, directly impacting productivity, operating costs, and operational variability. This article presents a layout optimization study using layout redefinition and computer simulation, applied to a garment manufacturing plant located in the gateway to the Bahia backlands. The methodology involved analyzing the current situation, mapping material flows, developing a proposed simulation model, and developing a layout alternative. Tecnomatix Plant Simulation software was used to evaluate the proposal, enabling modeling of the production flow and quantification of the gains obtained. The results indicated reduced variability in processing times, reduced lead time, and significant improvements in organization and operational comfort. The combined application of layout redefinition and computer simulation proved effective in identifying bottlenecks and streamlining production spaces, contributing to increased shop floor efficiency in the production flow under analysis. The study reinforces the importance of integrating classical production engineering methods with computer decision-making technologies.
Keywords: modeling and simulation; chronoanalysis; layout redefinition